Pengaruh Efisiensi dan Keamanan Terhadap Minat Nasabah Menggunakan Mobile Banking pada Bank Sumut Syariah Kantor Cabang Syariah Katamso Medan - Amanda Nabila; Pani Akhiruddin Siregar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test whether there is an influence of efficiency and security on customer interest in using mobile banking at Bank Sumut Syariah Medan Syariah. The population used in this research were customers of Bank Sumut Syariah Medan Syariah. The research results show that there is an influence between Efficiency and Security on the use of Mobile Banking at Bank Sumut Syariah Medan Syariah Branch.